THE The Influence Of Electronic Word Of Mouth (E-Wom) And Brand Trust On Brand Image And Shopee Consumers Buying Interest - Priyambodo Wahyu Jatmiko; Retno Widowati; Nuryakin Nuryakin (Jurnal Manajerial, 2023)
Background - The increase in sales on online platforms has increased since the Covid-19 pandemic began, during which period the government began implementing Large-Scale Social Restrictions (PSBB) so that the opportunity to travel to offline stores was very limited and customers did not have many choices but to fulfill their shopping needs online. Aim - This study aims to analyze the effect of e-WOM on brand image, the effect of brand trust on brand image, the effect of brand image on consumer buying interest, the effect of e-WOM on consumer buying interest, and analyze the role of brand image as mediating the effect of e-WOM and brand trust on consumer buying interest. Design /Methodology /Approach - This study uses a quantitative approach to investigate the influence between e-WOM, brand trust, consumer buying interest and brand image. The respondents of this study were shopee users. The questionnaire was distributed to 240 respondents. Then, the questionnaire data was analyzed using the Structural Equation Modeling (SEM) method with the Analysis of Moment Structure (AMOS) version 26.0 program. Findings - The analysis results show that the three hypotheses of this study are accepted. From this study it is evident that, there is a significant positive effect of e-WOM on brand image. In addition, there is also a significant positive effect of brand trust on brand image. Then there is a significant positive effect of e-WOM on buying interest. Meanwhile, brand image and brand trust have no effect on buying interest, and brand image cannot mediate the impact of e-WOM and brand trust on buying interest. Conclusion - e-WOM has a positive and significant effect on brand image, brand trust has a positive and significant effect on brand image, brand image has no effect on buying interest, e-WOM has a positive and significant effect on buying interest, brand trust has a positive and significant effect on buying interest, brand image has no effect as a mediator in the relationship between e-WOM and consumer buying interest, brand image has no effect as a mediator of the relationship between brand trust and consumer buying interest. Research implication - The results of this study indicate that e-WOM does not have a direct influence on purchase intention because it has to go through a mediating variable, namely brand image. Limitations - This research was only conducted on the people of Yogyakarta, thereby reducing the ability to generalize the research results.